2020
DOI: 10.1055/s-0040-1712466
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Problem List Use in Electronic Health Records—Application of the Unified Theory of Acceptance and Use of Technology

Abstract: Background Problem-oriented electronic health record (EHR) systems can help physicians to track a patient's status and progress, and organize clinical documentation, which could help improving quality of clinical data and enable data reuse. The problem list is central in a problem-oriented medical record. However, current problem lists remain incomplete because of the lack of end-user training and inaccurate content of underlying terminologies. This leads to modifications of diagnosis code descriptions and use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 34 publications
(53 reference statements)
0
23
0
Order By: Relevance
“…The in-depth interviews ensure rich and detailed information on the experiences and perceptions of interviewees (Oppong et al 2020). This method also allows researchers to investigate interviewees, attitudes, expectations, and concerns toward the implementation of AI innovation in religious education and practices (Wright and Headley 2021;Klappe et al 2020). The research separates the interviewees into six distinct groups, depending on their religious orientations and ages.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The in-depth interviews ensure rich and detailed information on the experiences and perceptions of interviewees (Oppong et al 2020). This method also allows researchers to investigate interviewees, attitudes, expectations, and concerns toward the implementation of AI innovation in religious education and practices (Wright and Headley 2021;Klappe et al 2020). The research separates the interviewees into six distinct groups, depending on their religious orientations and ages.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…The interview was recorded by both audio and written documents, ensuring the validity of responses. We also kept track of the similarity of answers on the same questions by different participants to strengthen the validity (Oppong et al 2020;Klappe et al 2020).…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…However, even if there is an established maintenance process to update terminologies in a way that they reach full coverage, studies show that other issues relating to terminology use should also be solved, e.g. a poor search-functionality could also be reason for perceived incompleteness [18,19]. A strength of our study is that it involved all relevant stakeholders and interviews were performed until saturation was reached, allowing us to assume that we captured all bottlenecks.…”
Section: Resultsmentioning
confidence: 99%
“…Healthcare providers consider free-text documentation typically as important, because they have concerns that by recording structured data on the problem list important information could be omitted [ 15 ]. As a consequence, when healthcare providers do code diagnoses on the problem list, they may modify the description of these diagnoses or add details in free-text fields as they often find the default diagnosis description insufficient or because they cannot find the diagnosis they are looking for [ 4 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The context of the diagnoses in modified descriptions is crucial for determining the clinical status of a patient [ 17 – 20 ]. Previous research showed that healthcare providers describe levels of certainty in clinical free text, e.g., to specify a working diagnosis [ 16 , 20 – 24 ]. Certainty levels vary from affirmed (certain) to non-affirmed (uncertain) levels of speculation.…”
Section: Introductionmentioning
confidence: 99%